Use of capacitive sensors with the instantaneous profile method to determine hydraulic conductivity - Almeida, Eurileny; Teixeira, Adunias; Rocha Neto, Odílio; Leão, Raimundo Alípio; Canafístula, Francisco José (Revista Ciência Agronômica, 2018)
Due to the need to monitor soil water tension continuously, the instantaneous profile method is considered laborious, requiring a lot of time, and especially manpower, to set up and maintain. The aim of this work was to evaluate the possibility of using capacitive sensors in place of tensiometers with the instantaneous profile method in an area of the Lower Acaraú Irrigated Perimeter. The experiment was carried out in a Eutrophic Red-Yellow Argisol. The sensors were installed 15, 30, 45 and 60 cm from the surface, and powered by photovoltaic panels, using a power manager to charge the battery and to supply power at night. Records from the capacitive sensors were collected every five minutes and stored on a data acquisition board. With the simultaneous measurement of soil moisture obtained by the sensors, and the total soil water potential from the soil water retention curve, it was possible to determine the hydraulic conductivity as a function of the volumetric water content for each period using the Richards equation. At the end of the experiment, the advantage of using capacitive sensors with the instantaneous profile method was confirmed as an alternative to using a tensiometer. The main advantages of using capacitive sensors were to make the method less laborious and to allow moisture readings at higher tensions in soils of a sandy texture.